Sphingosine 1-Phosphate- and C-C Chemokine Receptor 2-Dependent Activation of CD4+ Plasmacytoid Dendritic Cells in the Bone Marrow Contributes to Signs of Sepsis-Induced Immunosuppression - Smirnov, Anna; Pohlmann, Stephanie; Nehring, Melanie; Ali, Shafaqat; Mann-Nüttel, Ritu; Scheu, Stefanie; Antoni, Anne-Charlotte; Hansen, Wiebke; Büettner, Manuela; Gardiasch, Miriam J.; Westendorf, Astrid M.; Wirsdörfer, Florian; et al. (Frontiers in Immunology, 2017)
Sepsis is the dysregulated response of the host to systemic, mostly bacterial infection and is associated with an enhanced susceptibility to life-threatening opportunistic infections. During polymicrobial sepsis dendritic cells (DCs) secrete enhanced levels of interleukin (IL) 10 due to an altered differentiation in the bone marrow and contribute to the development of immunosuppression. We investigated the origin of the altered DC differentiation using murine cecal ligation and puncture (CLP), a model for human polymicrobial sepsis. Bone marrow cells were isolated after sham or CLP operation, the cellular composition was analyzed, and bone marrow-derived DCs (BMDC) were generated in vitro. From 24 h on after CLP, bone marrow cells gave rise to BMDC that released enhanced levels of IL-10. In parallel, a population of CD11chiMHCII+CD4+ DCs expanded in the bone marrow in a MyD88-dependent manner. Prior depletion of the CD11chiMHCII+CD4+ DCs from bone marrow cells in vitro reversed the increased IL-10 secretion of subsequently differentiating BMDC. The expansion of the CD11chiMHCII+CD4+ DC population in the bone marrow after CLP required the function of sphingosine 1-phosphate receptors and C-C chemokine receptor (CCR) 2, the receptor for C-C chemokine ligand (CCL) 2, but was not associated with monocyte mobilization. CD11chiMHCII+CD4+ DCs were identified as plasmacytoid DCs (pDCs) that had acquired an activated phenotype according to their increased expression of MHC class II and CD86. A redistribution of CD4+ pDCs from MHC class II- to MHC class II+ cells concomitant with enhanced expression of CD11c finally led to the rise in the number of CD11chiMHCII+CD4+ DCs. Enhanced levels of CCL2 were found in the bone marrow of septic mice and the inhibition of CCR2 dampened the expression of CD86 on CD4+ pDCs after CLP in vitro. Depletion of pDCs reversed the bias of splenic DCs toward increased IL-10 synthesis after CLP in vivo. Thus, during polymicrobial sepsis CD4+ pDCs are activated in the bone marrow and induce functional reprogramming of differentiating BMDC toward an immunosuppressive phenotype.